2022
DOI: 10.1021/acsnano.1c09208
|View full text |Cite
|
Sign up to set email alerts
|

Shape Matters in Magnetic-Field-Assisted Assembly of Prolate Colloids

Abstract: An anisotropic colloidal shape in combination with an externally tunable interaction potential results in a plethora of self-assembled structures with potential applications toward the fabrication of smart materials. Here we present our investigation on the influence of an external magnetic field on the self-assembly of hematite-silica core–shell prolate colloids for two aspect ratios ρ = 2.9 and 3.69. Our study shows a rather counterintuitive but interesting phenomenon, where prolate colloids self-assemble in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…Both D T and D R are indeed independent of the concentration, which confirms that 3D-DLS using the mod3D technique is capable of reliably suppressing multiple scattering effects and allows us to correctly determine translational and rotational diffusion coefficients for highly turbid suspensions with transmission values as low as around 1%. Using the TEM data as input, D T and D R were calculated using the theoretical approach of Ortega et al for elongated particles, and the results are also shown as the green line in Fig 9 . Given the known shape imperfections of these particles [36], the agreement between the theoretical calculation and the measured values is surprisingly good. Note that two alternative expressions for different geometrical models, ellipsoids and spherocylinders, as described in Martchenko et al [13], resulted in significantly larger discrepancies FIG.…”
Section: D-ddls Measurementsmentioning
confidence: 59%
“…Both D T and D R are indeed independent of the concentration, which confirms that 3D-DLS using the mod3D technique is capable of reliably suppressing multiple scattering effects and allows us to correctly determine translational and rotational diffusion coefficients for highly turbid suspensions with transmission values as low as around 1%. Using the TEM data as input, D T and D R were calculated using the theoretical approach of Ortega et al for elongated particles, and the results are also shown as the green line in Fig 9 . Given the known shape imperfections of these particles [36], the agreement between the theoretical calculation and the measured values is surprisingly good. Note that two alternative expressions for different geometrical models, ellipsoids and spherocylinders, as described in Martchenko et al [13], resulted in significantly larger discrepancies FIG.…”
Section: D-ddls Measurementsmentioning
confidence: 59%
“…For more details about this model, see the Methods section. Scattering intensities from MC simulations were obtained following a procedure already successfully used to describe reversible self-aggregation processes in other DNA-based systems and especially suitable for representing the hydrophobic (stacking) forces acting between G4 units. …”
Section: Resultsmentioning
confidence: 99%
“…To obtain more quantitative information on the G4 ensembles, we developed a novel approach comparing SAXS experimental intensities with those computationally estimated through Monte Carlo (MC) simulations, by modeling the G4 unit as a hard cylinder (HC) with two attractive sites at the basis, as schematized in Figure 2 (for more details see the Methods section). Scattering intensities from simulations of HCs have been obtained following a procedure similar to that discussed in Reference [36]. Within this procedure each cylinder is replaced with a set of scattering points randomly placed inside its volume with a fixed number density, and by using these points the structure factor is then calculated.…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%